SOMALIA 2007: STARTING FROM SCRATCH ON THE LONG AND WINDING ROAD TO PEACE AND DEMOCRACY? - Ansems, Adrienne (Scientia Militaria - South African Journal of Military Studies, 2011)
Somalia, a country composed of four and a half major tribes, namely the Hawiye, centred in Mogadishu, the Darod based in the North, the Dir and the Rahanweyn (the other 40-odd minor tribes falling into the “half” category) blundered into the 21st century without a modern state or its institutions (Mbugua, 2004:26). While the country has been without an effective government since 1991, recent reports suggest that, unless immediate action is taken on an international scale, Somalia will continue on its downward trend towards internal collapse. Although much hope was pinned on the success of the Somali National Reconciliation Conference, which played host to more than 1 325 delegates from a selection of Somalia’s various regions and clans to talk about and propose solutions to Somalia’s protracted problems, the conference was concluded on 30 August 2007 showing little for participants’ efforts. This initiative came after a spate of fighting in Somalia that has not only been labelled the “worst violence in Somalia’s 16 years of war and turmoil”, but also, “the worst single displacement of people this year anywhere in the world” (Nordland, 2007:60).